Muscle modes during shifts of the center of pressure by standing persons: effect of instability and additional support - Krishnamoorthy, Vijaya; Zatsiorsky, Vladimir M.; Latash, Mark L.; Scholz, John P. (Experimental brain research, 2004)
Muscle synergies in postural tasks have recently been studied using the framework of the uncontrolled manifold (UCM) hypothesis. A set of three hypothetical control variables, named M-modes, derived from the activity of 11 postural muscles, were identified. It was shown that postural synergies composed of these three M-modes preserve a certain shift of the center of pressure (COP) when subjects perform postural tasks while standing on a stable surface. In the present study we investigated the effects of support surface instability and availability of a light touch or grasp of a stable external support on the M-modes and their co-variation. The study was performed in two sessions. In the first session subjects released a load behind the body under four conditions: standing on a stable surface with no support (ST), standing on an unstable surface with no support (UN), standing on an unstable surface with a light touch (UN,T) and standing on an unstable surface with grasp of a stable object (UN,G). In the second session subjects performed two tasks: an arm movement backward and voluntary sway forward (towards the toes) under three conditions--ST, UN and UN,T. Principal component analysis was used to identify M-modes from data in the first session, and a UCM analysis was performed to study M-mode synergies in postural stabilization from data in the second session. A 'menu' of five M-modes was found, which were named either reciprocal M-modes or co-contraction M-modes based on the agonist-antagonist relationship of muscles comprising each mode. For a given task, subjects chose any three of these five M-modes in a subject- and task-specific manner. The reciprocal and co-contraction M-modes occurred equally frequently whether subjects stood on a stable or unstable support surface or whether a light touch was available or not. However, the co-contraction M-modes predominated when grasp of an object was available. In this condition, when the arm could be used for stabilization, there were M-modes uniting hip and shoulder muscles. However, the identified M-mode synergies were not found to lead to a consistent shift in the COP in any of the stability conditions. Possible reasons for this finding are discussed.